An Analysis of Sensory Stimulation Interventions in Music Therapy for Adults Living with Dementia: Four Case Studies - Shrader, Shelby (Voices: A World Forum for Music Therapy, 2024)
In this case report, four music therapists were observed and interviewed to identify the primary goals, characteristics, and perceived benefits of sensory stimulation interventions for adults living with dementia. Cases were described with regards to participant characteristics, goals, session context, ways participants were engaged, characteristics of the music, and benefits. Primary goals ranged from “any kind of response” to “to maintain the cognitive function of periodic orientation.” All cases included the use of receptive music therapy experiences with the use of live music via voice and a stringed instrument. Perceived benefits ranged from “increased alertness” to “increased tolerance of stimulation.” Analysis of these cases revealed a range of approaches to sensory stimulation rather than a single goal or intervention strategy. These diverse conceptualizations highlight the need for a stronger theoretical foundation, as well as further research, to enhance the meaningfulness of this intervention.